Application of GCMS and FTIR Fingerprinting in Discriminating Two Species of Malaysian Stingless Bees Propolis - Ibrahim, Nurhamizah; Jamil Zakaria, Abdul; Ismail, Zhari; Ahmad, Yusuf; Suryati Mod, Khamsah (International Journal of Engineering and Technology, 2018)
Propolis is a sticky substance made up of mixture of plant resin, wax and bee saliva. Propolis has been used in various health related problems as well as cosmetic ingredient.Â  This work was evaluating chemical fingerprint of Malaysian stingless bee propolis produced by two species, Heterotrigona itama (HI) and Geniotrigona thoracica (GT). Chemical fingerprint derived from fingerprint region (FR) of ATR-FTIR dataset of two types of extract, methanol (MHI, MGT) and ethanol (EHI, EGT). Principal component analysis and hierarchical cluster analysis was employed to discriminate the two species. The total variances account for FR was 95.63 % (PC1 = 54.01 %, PC2 = 41.61 %). EHI and EGT clustered closely between them and separately from MHI and MGT. HCA conform the grouping by PCA. GC-MS analysis revealed the presence of 20 different phytochemicals in methanol, while ethanol extract shown only 17 different phytochemicals of GT propolis. Meanwhile, 24 different phytochemicals were identified in methanol extract and 13 compounds presence in ethanol extract from propolis samples collected by HI species. Based on the good separation observed in both spectroscopic and chromatographic data, it seems reasonable to use chemical fingerprint coupled with chemometric analysis to differentiate two different species of stingless bee propolis. The findings from this study can be used as identification, classification and quality control methods for the profiling of propolisÂ Â